Pengaruh Strategi Positioning Dan Citra Destinasi Terhadap Keputusan Berkunjung Pada Dusun Kreatif Marindal - Siti Aisah; Edi Winata (CIVITAS: Jurnal Studi Manajemen, 2022)
The aims of this research are to analyze how much influence strategy of positioningand destination image to visiting decisions at Dusun Kreatif Marindal. The sampel sizeconsist of 114 respondents in destination with sample total. It provides whole of member ofthe population to be sample. Data analysis through multiple regression test, data processinguses SPSS. Results shows any effect of the positioning strategy and the image of destination tovisiting decisions. The conclusion of this research are proved that partial strategy ofpositioning has not effect to visiting decision but destination image has positive andsignificant influence on visiting decisions, simultaneous strategy of positioning anddestination image have positive and significant impact to visiting decisions.